Out-of-hospital Delivery: A Case Report - Songül Tomar Güneysu; Okşan Derinöz Güleryüz; Yasemin Men Atmaca; İlknur Fidancı; Özlem Çolak (Journal of Pediatric Emergency and Intensive Care Medicine, 2022)

(untitled)
Unplanned out-of-hospital birth is defined as a birth that occurs before arrival and without a planned midwife or medical doctor. The frequency of complications in mothers and babies is higher in unplanned deliveries out of hospital. Due to the shortness of the uterus and a history of bleeding at the 17th week, a 27-year-old mother who was administered betamethasone three times intermittently and her baby who was 22 weeks old were brought to the pediatric emergency service by ambulance, with the umbilical cord not separated from the clamped placenta between the legs of the mother. The baby was hypothermic at the first evaluation. The baby was immediately warmed up, the navel was clamped and separated from the placenta, and nasal oxygen therapy was initiated. While the body temperature was 35.5 °C at the 20th minute of birth; placed in a thermal bag, placed in a transfer incubator, connected to nasal continuous positive airway pressure, and admitted to the neonatal intensive care unit. On the 9th day of her follow-up, baby died due to apnea, desaturation, and resistant acidosis and hypotension. This case is presented in order to minimize the complications related to out-of-hospital delivery and to emphasize the necessity for the healthcare professionals to be adequately trained and equipped for delivery and neonatal resuscitation management, and to develop protocols between health and ambulance services.